Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965-2012: Archaeological assesment within the planned E4 motorway. - Swedish National Heritage Board, UV Öst (Uppsala University, 2020)
From 17/10/1990 to 08/11/1990 the Swedish National Heritage Board has performed investigations of five areas (named area 5-8 and 12/13) and one preliminary investigation of one area (named area 14) within the planned motorway of the E4 motorway, passing Norrköping.

In area 5, located at Borgs säteri, remains of residential nature was found. Ceramic finds give a possible dating of the Vendel period to the Viking age.

Area 6 is located next to Motala ström. Settlement remains were found, concentrated in the south part of the area.

Within area 7 a large settlement containing two areas of cultural layers were found. Ceramics place part of the ancient monument in the bronze age.

Area 8 also contained remains of residential nature, possibly from the iron age and the bronze age.

Area 12/13 is located east of the burial site RAÄ 15. 22 features with burned bones were found.

16 stone settings and possible stone settings previously unknown were discovered during the preliminary investigation of area 14. The previously known stone setting RAÄ 6 is located within the area.

The ZIP-file contains four shapefiles with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as ten geo-referenced maps (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

Riksantikvarieämbetet UV Mitt har under tiden 17/10/1990 till 08/11/1990 utfört utredningar av fem områden (benämnda omr 5-8 samt 12/13) och en förundersökning av ett område (benämnt omr 14) inom den planerade motorvägssträckningen av E4:an, förbifart Norrköping.

Inom område 5, beläget vid Borgs säteri, påträffades lämningar av boplatskaraktär. Keramikfynd ger en trolig datering till Vendeltid - Vikingatid.

Område 6 är beläget intill Motala ström. Boplatslämningar framkom inom området men en koncentration i södra delen av området.

Inom område 7 påträffades ett stort boplatsområde innefattande två områden med kulturlager. Keramik kan datera åtminstone delar av fornlämningen till bronsålder.

Även område 8 innehöll lämningar av boplatskaraktär, möjligen från järnålder och bronsålder.

Område 12/13 ligger strax öster om det registrerade gravfältet RAÄ 15. 22 anläggningar med brända ben påträffades i schakten.

Vid förundersökning av område 14 påträffades 16 stensättningar och troliga stensättningar som inte tidigare varit kända. Inom området ligger den tidigare kända stensättningen och skålgropslokalen RAÄ 6.

ZIP-filen innehåller data i form av fyra shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt tio georefererade kartor (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Arkeologiska utredningar inom den planerade motorvägssträcken av E4:an
Keywords: ceramics; keramik; finds; fynd; cup mark; skålgrop; excavation; utgrävning; HISTORY; HISTORIA; Archaeology; Arkeologi